Práticas e eventos de letramento acadêmico na iniciação à pesquisa no ensino médio: um estudo etnográfico-discursivo - Lemos, Claudênia de Paula (2022)
This thesis aims to investigate how the literacy practices present in the Iniciação à Pesquisa (IP) process carried out at the Núcleo de Trabalho, Pesquisa e Práticas Sociais (NTPPS) in High School in the state of Ceará are discursively constructed and textually materialized in a school full-time from Ceará. For this, I took as a basis studies on Academic Literacy (FIAD, 2016; LEA; STREET, 1998, 2006, 2014; LILLIS, 1999; TUSTING et al., 2019) anchored in New Literacy Studies (BARTON; HAMILTON, 1998; STREET, 1984, 2014), articulating them with the theoretical-methodological framework of Critical Discourse Analysis (CHOULIARAKI; FAIRCLOUGH, 1999; FAIRCLOUGH, 2001, 2003), textually oriented approaches that dialogue with each other regarding the concept of language as a social practice . The methodological procedures of this study were guided by Angrosino (2009), Blommaert and Jie (2010), Flick (2009), Magalhães (2000) and Magalhães, Martins and Resende (2017) and consisted of participant and non-participant observations, semi-structured interviews, focus groups and documentary data collection. The analysis was based on the scope of Textually Oriented Discourse Analysis (TODA), with emphasis on the analytical categories of discourse meanings (FAIRCLOUGH, 2001, 2003) and on the analytical categories of literacy events (HAMILTON, 2000). The results pointed to a constitution of the NTPPS as an academic literacy practice composed of three dimensions: institutional, situated/sociomaterial and discursive, which are constituted by discursive and non-discursive elements.